We don't swim here - Tirado, Vincent (Sourcebooks Fire, 2023)
"Bronwyn is only supposed to be in rural Hillwoods for a year. Her grandmother is in hospice, and her father needs to get her affairs in order. And they're all meant to make some final memories together. Except Bronwyn is miserable. Her grandmother is dying, everyone is standoffish. All she hears are warnings about going in the water, despite a gorgeous lake. And a pool at the abandoned rec center. And another in the high school basement. Anais tries her hardest to protect Bronwyn from the shadows of Hillwoods. She follows her own rituals to avoid any unnecessary attention--and if she can just get Bronwyn to stop asking questions, she can protect her too. She doesn't get that the lore is, well, truth. The living ones aren't the only ones who seek retribution when they're wronged. But when Bronwyn does more exploring than she should, they are both in for danger they couldn't expect"--Dust jacket flap.